2016
DOI: 10.1093/scan/nsw059
|View full text |Cite
|
Sign up to set email alerts
|

Mirroring multiple agents: motor resonance during action observation is modulated by the number of agents

Abstract: Although social situations regularly involve multiple persons acting together, research on the mirror neuron system has focused on situations in which a single agent is observed. Therefore, the goal of the current study was to explore the role of the mirror mechanism in situations involving multiple agents. Specifically, we used transcranial magnetic stimulation (TMS) to investigate whether mirror activation is modulated by the number of observed agents. Based on group contagion research, we hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
47
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 46 publications
10
47
1
Order By: Relevance
“…Simulation 1 aims to reproduce the first finding of Cracco et al (2015), namely that two hands performing the same action (2H ID) produce a stronger congruency effect than one hand performing a single action (1H). More specifically, it does so by implementing the hypothesis that identical actions activate the same motor representation (Cracco & Brass, 2018c, 2018aCracco et al, 2015Cracco et al, , 2016. As shown in Figure 3, the model captures the empirical results, with responses on congruent trials being faster and responses on incongruent trials being slower in the 2H ID condition than in the 1H condition.…”
Section: Simulationmentioning
confidence: 70%
See 1 more Smart Citation
“…Simulation 1 aims to reproduce the first finding of Cracco et al (2015), namely that two hands performing the same action (2H ID) produce a stronger congruency effect than one hand performing a single action (1H). More specifically, it does so by implementing the hypothesis that identical actions activate the same motor representation (Cracco & Brass, 2018c, 2018aCracco et al, 2015Cracco et al, , 2016. As shown in Figure 3, the model captures the empirical results, with responses on congruent trials being faster and responses on incongruent trials being slower in the 2H ID condition than in the 1H condition.…”
Section: Simulationmentioning
confidence: 70%
“…Pointing in this direction, research looking at automatic imitation of multiple agents has shown that seeing two hands performing the same action elicits stronger corticospinal excitability (Cracco, De Coster, Andres, & Brass, 2016) and therefore stronger imitation (Cracco & Brass, 2018a;Cracco, De Coster, Andres, & Brass, 2015) than seeing one hand performing a single action. Similarly, research using four stimulus hands has shown that automatic imitation increases proportionally with the number of identical observed actions (Cracco & Brass, 2018c).…”
Section: Introductionmentioning
confidence: 99%
“…In the same way that we cannot refrain from recognizing a face or a word when we perceive it, we cannot help but represent in motor terms the actions we perceive. During interactions with humans, the information that leads to this activity is integrated automatically [48], [49] and is resistant to modulation by context [50], [51]. This system could be used to anticipate other people's actions [52].…”
Section: The Change In the Intrinsic Representation Of Robotsmentioning
confidence: 99%
“…Instead, to reach this conclusion, it has to be shown that multiple motor representations were activated. Therefore, in previous work, we have measured automatic imitation (Cracco et al 2015;Brass 2018a, 2018b) and corticospinal excitability (Cracco et al 2016) while participants observed either a single action or two identical actions. This revealed action-specific increases in both measures when two identical actions were observed, suggesting that both actions triggered the same motor representation.…”
mentioning
confidence: 99%